Effect of Gas Exchange Interval on CH4 Recovery Efficiency and Study of Mechanism of CH4 Hydrate Replacement by CO2 Mixture - Ding, Ya-Long; Wang, Hua-Qin; Lv, Tao (Frontiers in Energy Research, 2021)
As an environment-friendly natural gas hydrate exploitation method, CO2 replacement method can not only achieve the purpose of mining natural gas hydrate, but also store the current greenhouse gas CO2 in the form of hydrate on the seabed, and maintain the stratum stability of hydrate deposit area. In order to improve the rate and efficiency of CH4-CO2 replacement reaction, researchers proposed to use CO2 contained gas mixture instead of pure CO2 to replace CH4 in natural gas hydrate. Based our previous work about CH4 hydrate recovery with 40% CO2 + 60% H2, in this study, the effect of gas concentration in gas phase on final CH4 recovery are investigated by implying different time interval of gas exchange operation. Experimental results show that The CH4 recovery efficiency is 10.41 when the gas exchange is continues through the whole replacement process, and CH4 recovery efficiency changes to 12.25, 32.24 and 28.86 when gas exchange operation is carried out every 12, 24, 36 h. Indicating that replaced CH4 needs to be discharged in time to avoid CH4 molecules being replaced to form hydrates again, and it is necessary to accurately control the time interval of gas exchange operation to avoid insufficient contact time between CO2 and H2 molecules and CH4 hydrate, which affects the final replacement efficiency. In addition, the mechanism of CO2 gas mixture containing small gas molecule such as H2, N2 are studied. The results indicate that when CO2 containing small molecules such as H2 and N2 displace CH4 hydrate, the existence of small molecules (H2, N2) can give rise to decompose the hydrate lattice and release CH4 gas. If the gas molecules (CO2, N2, H2, CH4) in the gas phase have enough driving force to enter the hydrate lattice and remain stability, CH4 hydrate will not decompose completely; If not, CH4 hydrate will be completely decomposed.